Separation of amino acids from their mixture by facilitated pertraction with D2EHPA - Blaga, Alexandra-Cristina (Array, 2008)
Summary: The study on facilitated pertraction of some amino acids with D2EHPA as carrier underlined the significant influence of the pH gradient between the aqueous phases, carrier concentration and mixing intensity. The amino acids can be separated selectively by varying the pH value of feed phase, due to the formation of the corresponding ionic species. The increase of the carrier concentration inside the liquid membrane leads to the intensification of the initial and final mass flows. The amplitude of this effect depends on the molecular size of the pertracted amino acid. The permeability factors are positively influenced by the increase of the pH value of feed phase and rotation speed of the stirrers in the aqueous phases, but are negatively affected by the increase of the stripping phase pH. For all studied amino acids, the pertraction system reaches its maximum capacity of solute transfer at = 60 g L–1 carrier concentration